Age‐related differences when measuring political hypocrisy. Issue 4 (16th April 2018) - Prete, M. Irene; Guido, Gianluigi; Pichierri, Marco; Harris, Phil
Abstract : This article aims to develop a scale for measuring political hypocrisy (conceptualized as the inconsistency between values publicly expressed by politicians and the behavior they actually demonstrate) and to explore the role of age in voters' perceptions of politicians' hypocrisy, analyzing if citizens belonging to different age groups may identify politicians' hypocrisy with a different detail. Results show that the 19‐item scale of political hypocrisy—composed of three dimensions, called "ambiguity, " "slyness, " and "deceit"—has good psychometric properties, and that age‐related differences when measuring political hypocrisy do exist (young voters show a greater awareness of the hypocritical behavior held by politicians). Furthermore, results suggest that the perception of political hypocrisy may vary according both to voters' political orientation and voting intention.